Meme culture and social media as gendered spaces of dissent and dominance. Issue 3 (2nd October 2021) - Kumari, Sapna
Abstract: Technology mediated communication has promulgated the usage of widespread images on social media under the guise of generating humour/irony. On the one hand, these handles are being utilized to voice stimulating issues; on the other, they can be held accountable for perpetrating distressing conditions for girls/women who face hostile rhetoric at work against them. Mansplaining, anti-feminist and off the mark comments filtered through memes are common and become carriers of mishandled social, cultural, racial and political tropes. The proposed paper attempts to critique visual misrepresentation and misreadings of tropes/messages channelized through memes on social media, alongside the study the scope of visual literacy at the intersections of feminist media studies. This can lead to a more nuanced understanding of meme culture as spaces for dominance and counter narratives of misogyny. The paper draws on theories and conceptual frameworks developed in the field of cultural studies, visual studies, communication studies and offers an interconnected critique of the subject.